Transformasi Digital Dalam Praktik Akuntansi Lingkungan: Peluang dan Tantangan Dalam Dunia Bisnis Modern - Ni Wayan Apriyani; Ni Putu Angelita Yudia Maharani; Ni Komang Astini; Ni Made Ari Partiwi (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2025)
Digital transformation has brought significant changes to environmental accounting practices, offering both opportunities and challenges for the modern business world. This article analyzes the impact of digitalization on operational efficiency, financial reporting accuracy, and data-driven decision-making, with a focus on technologies such as cloud computing, blockchain, and artificial intelligence (AI). The research method used is descriptive analysis based on a literature review of accredited journals and scientific articles published between 2021 and 2025. The results show that digitalization increases transparency, process automation, and speeds up real-time data access, but also faces challenges such as infrastructure investment, data security, and the digital literacy gap. Collaboration between industry, academia, and regulators is needed to address these challenges and ensure the ethical and sustainable use of technology. In conclusion, digital transformation in environmental accounting has the potential to boost companies' competitive advantage, provided it is supported by human resource readiness, visionary leadership, and a holistic adaptation strategy.